Sort sourceof pea in Ukraine and in the world - А. М. Шевченко (Plant Varieties Studying and Protection)
The sorts different by economic-biologic character of unshed seed, breeded in Ukraine and abroad obtained wide spreading in production. Expediency using lugansky or samarsky type of determinant stability to healthy growth. Breeding sorts with tendril type of leaf give the positive results in increase stability of the plants to damping-off. The sorts combining named recessive character with another aconomic-value traits of grain pea made and suggested to production.